New golden age - Batra, Ravi (New York, 2007)
In The New Golden Age, bestselling author and economist Ravi Batra identifies the roadblocks to economic prosperity--and what we need to do to overcome them. Bringing the same insight and expertise that made books like The Downfall of Capitalism and Communism international bestsellers, Batra takes on falling minimum wages, corporate scandals, rocketing oil prices, and many of the other crises facing the world economy. He also offers an expansive, optimistic vision of how the international community can address them and bring about something historically unprecedented: true global economic prosperity.
Keywords: Political corruption - Economic aspects